Hair cortisol concentrations and cortisol stress reactivity predict PTSD symptom increase after trauma exposure during military deployment. (September 2015) - Steudte-Schmiedgen, Susann; Stalder, Tobias; Schönfeld, Sabine; Wittchen, Hans-Ulrich; Trautmann, Sebastian; Alexander, Nina; Miller, Robert; Kirschbaum, Clemens
Highlights: Predictive value of cortisol for PTSD symptom development upon trauma investigated. Prospective study: soldiers before deployment and 12-month post-deployment. Two endocrine markers: hair cortisol and salivary cortisol stress reactivity. Lower cortisol activity predictive of a greater increase in PTSD symptomatology. Summary: Background: Previous evidence on endocrine risk markers for posttraumatic stress disorder (PTSD) has been inconclusive. Here, we report results of the first prospective study to investigate whether long-term hair cortisol levels and experimentally-induced cortisol stress reactivity are predictive of the development of PTSD symptomatology in response to trauma during military deployment. Methods: Male soldiers were examined before deployment to Afghanistan and at a 12-month post-deployment follow-up using dimensional measures for psychopathological symptoms. The predictive value of baseline (i) hair cortisol concentrations (HCC, N = 90) and (ii) salivary cortisol stress reactivity (measured by the Trier Social Stress Test, N = 80) for the development of PTSD symptomatology after being exposed to new-onset traumatic events was analyzed. Results: Baseline cortisol activity significantly predicted PTSD symptom change from baseline to follow-up upon trauma exposure. Specifically, our results consistently revealed that lower HCC and lower cortisol stress reactivity were predictive of a greater increase in PTSD symptomatology in soldiers who had experienced new-onset traumatic events (explaining 5% and 10.3% of variance, respectively). Longitudinal analyses revealed an increase in HCC from baseline to follow-up and a trend for a negative relationship between HCC changes and the number of new-onset traumatic events. Additional pre-deployment analyses revealed that trauma history was reflected in lower HCC (at trend level) and that HCC were negatively related to stressful load. Conclusions: Our data indicate that attenuated cortisol secretion is a risk marker for subsequent development of PTSD symptomatology upon trauma exposure. Future studies are needed to confirm our findings in other samples.